Ali lahko z novimi protimikrobnimi učinkovinami zmagamo v boju z bakterijami? - Obreza, Aleš (Farmacevtski vestnik, 2020)
It is a well-known saying that history is the best teacher for the future. This also applies to the field of pharmaceutical chemistry, narrowly defined as design, synthesis and evaluation of new drug candidates. Antimicrobials reflect the continued desire of mankind to successfully fight with the diseases that have been the main cause of high mortality and short life expectancy in the past. Since a very successful period of control of bacterial infections is reaching the end, the search for new molecules for the future is very important. Despite its small size at the global level, the Chair of pharmaceutical chemistry has done excellent research work over the past two decades, with a number of top results and publications in this field.
Keywords: Bakterijska rezistenca; Farmacevtska kemija; protimikrobne učinkovine